A Companion to Environmental Philosophy - Jamieson, Dale; Jamieson, Dale (Blackwell Publishing, 2001)
A Companion to Environmental Philosophy is a pioneering work in the burgeoning field of environmental philosophy. This ground-breaking volume contains thirty-six original articles exemplifying the rich diversity of scholarship in this field. Contains thirty-six original articles, written by international scholars. Traces the roots of environmental philosophy through the exploration of cultural traditions from around the world. Brings environmental philosophy into conversation with other fields and disciplines such as literature, economics, ecology, and law.
English
Keywords: GE1-350 Environmental Sciences